The Impact of Public Capital Investments on the Revenue Growth of Medium Enterprise in Indonesia - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2012)
Abstract: Public capital investment represents t.he role of state and local governments in supporting greater capacity of private enterprises to gain success in a market economy measured by revenue growth. Medium enterprises are considered as the catalysts for economic growth and competitiveness particularly in developing countries due to efficiency and flexibility in an adverse economic environment. Using aggregate data of 30 states (provinces) in Indonesia from 1997-2002, the impact of public capital investment on the revenue growth of medium enterprise is examined. The paper finds that only medium enterprises in the industrial and trading sector benefited from public capital investments and the most optimum capital investment is in transport infrastructure.